2019
DOI: 10.3389/fphar.2019.01095
|View full text |Cite
|
Sign up to set email alerts
|

Shengmai Injection Suppresses Angiotensin II-Induced Cardiomyocyte Hypertrophy and Apoptosis via Activation of the AMPK Signaling Pathway Through Energy-Dependent Mechanisms

Abstract: Shengmai injection (SMI), a traditional Chinese herbal medicine extracted from Panax ginseng C.A. Mey., Ophiopogon japonicus (Thunb.) Ker Gawl., and Schisandra chinensis (Turcz.) Baill., has been used to treat acute and chronic heart failure. This study aimed to further clarify the effects of SMI on energy metabolism. SMI could improve cell-survival rate and also reduce myocardial cell hypertrophy and apoptosis. Mitochondria are important sites of cellular energy metabolism, and SMI protects mitochondrial fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 48 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…extracts. It inhibits myocardial cell hypertrophy and apoptosis by activating the AMPK energy-dependent signaling pathway 195 . Shenfu granules are composed of Panax ginseng C.A.…”
Section: Potential Drugs For Reducing Hf By Regulating Energy Metabolismmentioning
confidence: 99%
“…extracts. It inhibits myocardial cell hypertrophy and apoptosis by activating the AMPK energy-dependent signaling pathway 195 . Shenfu granules are composed of Panax ginseng C.A.…”
Section: Potential Drugs For Reducing Hf By Regulating Energy Metabolismmentioning
confidence: 99%
“…Ker Gawl., and Schisandra chinensis (Turcz.) Baill., can activate the AMPK signaling pathway [ 103 ]. As AMPK regulates FUNDC1 expression, targeting AMPK may provide a cardioprotective effect.…”
Section: Discussionmentioning
confidence: 99%
“…The biological pathway analysis helps reveal what biological reactions that drug intervention can trigger, and it is most important for guidance of therapeutic target discovery and treatment strategy suggestion. Some pharmacological studies reported SMI’s effects of anti-inflammatory, anti-oxidation, and suppression of cell apoptosis through pathways such as caspase-3, mTOR, JNK, AKT, ERK1/2, and AMPK ( Li et al, 2019 ; Zhu et al, 2019 ; Cao et al, 2020 ). Recently, Jiang et al ( Jiang et al, 2020 ) used systemic pharmacology and chemoinformatics to predict signaling pathways, biological processes, and targets of Shengmai Yin (including SMI) therapeutic role in coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…SMI prevented myocardial ischemia reperfusion injury by reducing myocardial apoptosis and enhancing vascular endothelial growth factor (VEGF)–related angiogenesis ( Lin et al, 2018 ). In addition, the related mechanism studies revealed SMI alleviated oxidative stress by activation of AKT and inhibition of ERK pathways ( Zhu et al, 2019 ) and suppressed cardiomyocyte hypertrophy via activation of the AMPK signaling pathway ( Li et al, 2019 ). However, all these studies focusing on SMI’s minority action targets and its comprehensive regulation mechanisms with the nature of multicomponent and multi-target are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%